Value Innovation Creation in a Creative Industries Platform - Pavlovaitė, Ugnė (Vilnius University Open Series, 2022)
Studying modern organisational management models shows an increasing researchers’ interest in innovation and business transaction development in various industries based on platforms (Lew et al., 2019). Rapid establishment of platforms (hereinafter – platformisation) is defined as a process where economic, governmental and digital infrastructures are expanded into virtual ecosystems (Nieborg and Poell, 2018). However, it is important to emphasise that from the cognitive point of view, platforms can be established on the basis of an organisational structure as well; this is based on collective activities, dynamics and interconnection. The concept of the platform is interpreted as a new organisational paradigm due to changed expectations of those interested in order to increase the efficiency of an organisation (Kim, 2016). The aspect of new value generation is often compared with innovation and application of a platform strategy in organisations. In the academic discourse, value innovation has been studied for over two decades; however, researchers have found out that when competitiveness of organisations increases in various sectors, there has been a need to ensure as much as possible a position in the current market, employing less methods that require economic input that would allow to develop the quality of services or products when offering innovation. Innovation development processes used in creative industries are seen as a critical source of a long term competitive advantage (Holmquist et al., 2019). Evaluating the ability of CIs organisations to use existing resources in the market effectively, new ways and methods that give basis to general value generation through creative activities are created. Regarding both the practical and the academic need to study value innovation creation in a creative industries (CIs) platform, evaluating the context of the changing environment, the following research problem has been formulated: how is value innovation created in a creative industries platform?The work presents the analysis of academic discourse: abstract and systematic theoretical material of value innovation creation in a creative industries platform.The aim of the article is to analyse the creation of value innovation in a creative industries platform.
Keywords: value innovation; creative industries; platform; creation